Research on the Constraints and Optimization Path of Student Safety Management in Undergraduate Colleges and Universities in Sichuan Province - Zhang, Changshun; Zhang, Jinqiu (International Journal of Social Sciences and Public Administration, 2024)
Strengthening the safety management of universities and creating a safe campus are necessary guarantees for promoting high-quality development of universities. They also have a positive role in ensuring students' personal safety and maintaining campus harmony and stability. Taking undergraduate colleges in Sichuan Province as an example, this article analyzes the constraints faced by undergraduate colleges in implementing regulations and systems, building safety culture, empowering information technology, and promoting multi-party cooperation in carrying out safety management. Specific policy recommendations are proposed around four optimization paths: strengthening the implementation of regulations and systems, deepening safety culture construction, enhancing information technology integration, and promoting social environment cooperation.